Combining Oxidative Torrefaction and Pyrolysis of Phragmites australis: Improvement of the Adsorption Capacity of Biochar for Tetracycline - Jiang, Shilin; Tan, Mengjiao; Huang, Zhongliang; Hu, Jinguang; Li, Changzhu; Lei, Tingzhou; Zhang, Xuan; Wu, Zijian; Huang, Jing; Qin, Xiaoli; Li, Hui (Frontiers in Energy Research, 2021)
The objective of this study was conceived to evaluate the effect of oxidative torrefaction on PAS biochar characteristics and its adsorption capacity for TC. The oxidative torrefaction combined with pyrolysis of Phragmites australis (PAS) was carried out, and the physicochemical properties of PAS biochar were characterized. Subsequently, the effects of adsorbent dosage, initial TC concentration, salinity, and temperature on TC adsorption capacity by PAS biochar were evaluated, and the results of kinetic, equilibrium, and thermodynamic studies were used to assess the mechanism of adsorption. The results showed that the biochar derived from oxidatively torrefied PAS pyrolysis (TPBC) contained higher specific surface area, stronger hydrophobicity, and lower ash content than the biochar derived from raw PAS pyrolysis (PBC). Compared with PBC, TPBC showed higher adsorption capacity for tetracycline (TC). The adsorption kinetic was more in line with the pseudo-second-order model. The adsorption rate by PAS biochar was controlled not only by external mass transfer but also by intraparticle diffusion, and the adsorption process is favorable and irreversible adsorption. Moreover, the dominant adsorption nature will be physical, and the organic functional groups of PAS biochar will participate in the adsorption process. In summary, the oxidative torrefaction could be an effective approach to improve the adsorption capacity of PAS biochar for TC.